Endoplasmic Reticulum Membrane and Contact Site Dynamics in Autophagy Regulation and Stress Response - Morel, Etienne (Frontiers in Cell and Developmental Biology, 2020)
Autophagy mobilizes a variety of intracellular endomembranes to ensure a proper stress response and the maintenance of cellular homeostasis. While the process of de novo biogenesis of pre-autophagic structures is not yet fully characterized, the role of the endoplasmic reticulum (ER) appears to be crucial in early steps of autophagic process. Here, I review and discuss various aspects of ER and ER driven membrane contact sites requirement and impact on mammalian organelles and endomembranes biogenesis, in particular during the early steps of autophagy-related membrane dynamics.